Information Services, Private Bureaucracies, and Japan's Comparative Advantage - Engelbrecht, Hans-Jurgen (The Review of Economics and Statistics, 1991)
This note investigates the determinants of Japan's manufacturing trade structure in 1980. They include variables derived from an information economy perspective as well as traditional trade variables. Estimates for variables approximating organizational inefficiency indicate that even in Japan, which is reported to often have smaller private bureaucracies than the United States, relatively large bureaucracies have a negative effect on trade performance. Human capital intensity is found to have a positive effect on Japan's comparative advantage and exports. The importance of R&D expenditure is confirmed. Copyright 1991 by MIT Press.